Взаємозв'язок між соціально-економічними трансформаціями та формуванням нової якості життя - Хандій, О.О.; Шамілева, Л.Л.; Кобцева, Д.А. (Вісник економічної науки України, 2021)
У статті досліджено вплив соціально-економічних трансформацій на формування базових умов життєдіяльності та життєзабезпечення в системі формування нової якості життя. Визначено зовнішні та внутрішні чинники, які формують середовище соціоекономічних перетворень і мають різноспрямовані вектори впливу на забезпечення стабільних та збалансованих умов життєдіяльності. Виділено соціоекономічні перетворення, які під впливом деструктивних чинників стримують можливості забезпечення гідних умов життєдіяльності та становлення нової якості життя. Виявлено причинно-наслідкові зв’язки чинників та умов формування нової якості життя. Ґрунтуючись на виявлених взаємозв’язках, уточнено визначення поняття «якості життя». Систематизовано основні складові соціоекономічних перетворень. Обґрунтовано базові умови життєдіяльності та життєзабезпечення. Запропоновано основні структурні елементи нової якості життя за умов соціоекономічних перетворень. В статье исследовано влияние социально-экономических трансформаций на формирование базовых условий жизнедеятельности и жизнеобеспечения в системе формирования нового качества жизни. Определены внешние и внутренние факторы, которые формируют среду социоэкономических преобразований и имеют разнонаправленные векторы влияния на обеспечение стабильных и сбалансированных условий жизнедеятельности. Выделены социоэкономические преобразования, которые под воздействием деструктивных факторов сдерживают возможности обеспечения достойных условий жизнедеятельности и становления нового качества жизни. Выявлены причинно-следственные связи факторов и условий формирования нового качества жизни. Основываясь на выявленных взаимосвязях, уточнено определение понятия «качество жизни». Систематизированы основные составляющие социоэкономических преобразований. Обоснованы базовые условия жизнедеятельности и жизнеобеспечения. Предложены основные структурные элементы нового качества жизни в условиях социоэкономических преобразований. Globalization forms a new geostrategic reality, determines the patterns of development of the modern world, affects the emergence of new value coordinates, transforms social, political, economic and public administration systems, changing living conditions and livelihoods. The purpose of the work is to determine the relationship between socio-economic transformations and the formation of a new quality of life. The article examines the impact of socio-economic transformations on the formation of basic living conditions and livelihood in the system of formation of a new quality of life. Under the transformation in various spheres of public life are considered special changes that determine the qualitative changes in the nature of processes or phenomena. Socio-economic transformations are the result of appropriate transformation processes. External and internal factors that form the environment of socio-economic transformations and have different vectors of influence on ensuring stable and balanced living conditions are identified. Socio-economic transformations are singled out, which under the influence of destructive factors constrain the possibility of providing decent living conditions and the formation of a new quality of life. Causal links between factors and conditions for the formation of a new quality of life have been identified. Based on the identified relationships, the definition of "quality of life" is clarified. Under the quality of life it is proposed to understand the objective consequences of the impact of a set of living conditions and life activities that determine the physical, economic, mental and social well-being of man. The main components of socio-economic transformations are systematized. The basic conditions of life and livelihood are substantiated. The main structural elements of the new quality of life under the conditions of socio-economic transformations are offered. It is concluded that the formation of a new quality of life is the result of the causal process of socio-economic transformations and this necessitates constant diagnostics of the socio-economic environment and assessment of its main parameters and disclosure of the nature of relationships.